Purification, characterization and kinetic properties of alpha-naphthyl acetate esterase from wheat flour (Triticum aestivum) - Jameel, Ahmad Tariq; Soropogui, Keamou M. (Elsevier, 2018)
Plant-esterase from wheat flour was purified via aqueous two-phase system (ATPS). The enzyme crude extract was first filtered through a polyethersulfone OmegaTM ultrafiltration membrane, followed by two-step ATPS with PEG1000, NaH2PO4 and (NH4)2SO4. Based on previous studies, the first ATPS consisting of 27.0% PEG1000 and 13.0% NaH2PO4 (w/w) was performed at room temperature and pH 5.0. The top phase was carefully separated, and 6.0% (NH4)2SO4 (w/w) was added to form the second phase system under similar conditions, to obtain the pure enzyme that partitioned in the bottom salt phase. The purification thus obtained was 10.35 fold with an enzyme yield of 72.90%. Sodium dodecylsulphate polyacrymamide gel electrophoresis (SDS-PAGE) was used to estimate the molecular weight of the target esterase to be around 68 kilo Daltons (kDa). Using a 16 mM solution of alpha naphthyl acetate as substrate, the maximum activity of the purified enzyme, alpha naphthyl acetate esterase (ANAE) was found to be 0.78 U at the optimum conditions of 40 ◦C and pH 8.0 for 15 min of incubation. The Michaelis–Menten parameters Km and Vmax of the purified enzyme were estimated using Langmuir linear plot as 22.5 mM and 4.71 U mg−1, respectively. Further purification was obtained by dialyzing the bottom ANAE rich phase in a solution of 0.04 M phosphate buffer with pH 6.5 to remove the salt, which was then concentrated using centrifugal tubes with OmegaTM membrane. The highly pure ANAE so obtained was immobilized on the multiwalled carbon nanotube for the development of inhibition based enzyme biosensors for pesticides detection.